Haplotype analyses of haemoglobin C and haemoglobin S and the dynamics of the evolutionary response to malaria in Kassena-Nankana District of Ghana. - Ghansah, A; Rockett, K; Clark, T; Wilson, MD; Koram, K; Oduro, A; Amenga-Etego, L; Anyorigiya, T; Hodgson, A; Milligan, P; Rogers, W; Kwiatkowski, D (2012)
Haemoglobin S (HbS) and C (HbC) are variants of the HBB gene which both protect against malaria. It is not clear, however, how these two alleles have evolved in the West African countries where they co-exist at high frequencies. Here we use haplotypic signatures of selection to investigate the evolutionary history of the malaria-protective alleles HbS and HbC in the Kassena-Nankana District (KND) of Ghana.